The Role of Tax Depreciation for Investment Decisions: A Comparison of European Transition Countries - Chang Woon Nam; Doina Maria Radulescu (Center for Economic Studies and ifo Institute (CESifo), 2003)
This study compares incentive effects of various tax depreciation methods currently adopted in European transition economies. In these countries straight-line, geometric-degressive and accelerated depreciation measures are quite popular in combination with different corporate tax rates. Their generosity is determined on the basis of Samuelson's true economic depreciation. For this purpose, the present value model is applied under the particular consideration of different financial structures. In this context the traditional Modigliani-Miller theorem for capital structure is revisited. Furthermore, the aspect of inflation is integrated into the model. The central issue is that the historical cost accounting method generally applied for the calculation of the corporate tax base causes fictitious profits in inflationary phases that are also taxed. Therefore, in an inflationary period generous tax depreciation provisions do not promote private investment as designed, but partly compensate such additional tax burdens caused by inflation.
Keywords: 330; true economic depreciation; tax depreciation rules; corporate tax; investment decision; financial structure; net present value model; inflation; transition economies